Tri-klo (2024)
Problem solving is an essential skill that applies throughout life (Paenza, 2012). Every day, we we face challenges inherent to our existence and we must find solutions using the tools at our provision. Similarly, industrial design addresses the problems depending on the occasion, where knowledge applied conforms to the specific need (Saints, 2014).